2012
DOI: 10.1371/journal.pone.0044857
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Disorders in a Post War British Cohort Reaching Retirement: Evidence from the First National Birth Cohort Study

Abstract: BackgroundThe medical needs of older people are growing because the proportion of the older population is increasing and disease boundaries are widening. This study describes the distribution and clustering of 15 common clinical disorders requiring medical treatment or supervision in a representative British cohort approaching retirement, and how health tracked across adulthood.Methods and FindingsThe data come from a cohort of 2661 men and women, 84% of the target sample, followed since birth in England, Scot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
0
35
1
Order By: Relevance
“…Together with the previous observations of smaller size and bone mass in men in this cohort, these are all features found to be risk factors for fracture of the femoral neck attributed to osteoporosis . Although osteoporosis was prevalent at other sites in this cohort, there was no evidence of hip osteoporosis in individuals included in this study (minimum Z ‐score −2.4) and few fractures; therefore, associations between walking age, hip shape, and fractures could not be explored. There was no effect of adjustment for hip BMD on associations between walking age and hip shape, although only weak associations between hip BMD and hip mode scores in this cohort have been reported .…”
Section: Discussioncontrasting
confidence: 59%
“…Together with the previous observations of smaller size and bone mass in men in this cohort, these are all features found to be risk factors for fracture of the femoral neck attributed to osteoporosis . Although osteoporosis was prevalent at other sites in this cohort, there was no evidence of hip osteoporosis in individuals included in this study (minimum Z ‐score −2.4) and few fractures; therefore, associations between walking age, hip shape, and fractures could not be explored. There was no effect of adjustment for hip BMD on associations between walking age and hip shape, although only weak associations between hip BMD and hip mode scores in this cohort have been reported .…”
Section: Discussioncontrasting
confidence: 59%
“…At age 60–64, we used a count of the number of clinical disorders (0, 1, 2, 3, 4, 5+) as a measure of recent health status [26]. To be included in this variable, study members required complete data on many health variables from the postal questionnaire and the home or clinic visit; therefore we included an item missing category.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that, on average, study participants had at least two out of fifteen common clinical disorders assessed at age 60–64 years, and less than one in six were disorder free ( 97 ) . Using cross-sectional data at 60–64 years, associations between each measure of physical capability and many of these fifteen disorders are observed; Fig.…”
Section: Suggestions For Future Researchmentioning
confidence: 99%